Quarantine During COVID-19 Outbreak: Eating Behavior, Perceived Stress, and Their Independently Associated Factors in a Brazilian Sample - Liboredo, Juliana Costa; Anastácio, Lucilene Rezende; Ferreira, Lívia Garcia; Oliveira, Lívya Alves; Della Lucia, Ceres Mattos (Frontiers in Nutrition, 2021)
The study aimed to assess the eating behavior (uncontrolled eating; emotional eating; cognitive restraint), the perceived stress, and independently associated factors among Brazilians during the COVID-19 pandemic. . An online survey was conducted and data about 1368 participants were evaluated. Multivariate logistic regression models were performed to identify factors independently associated (socioeconomic, lifestyle, and eating habits data) with eating behaviors and perceived stress. Working in the COVID-19 frontline (OR=2.19); increased food delivery (OR=1.49); increased food intake (OR=1.48), increased number of meals (OR=1.13), and emotional eating (OR=1.05) were factors independently associated with uncontrolled eating. Variables that were independently associated with emotional eating were: increased food intake (OR=2.57); graduation in a non-health-related course (OR=1.78); perceived stress (OR=1.08); uncontrolled eating (OR=1.07) and cognitive restraint (OR=1.02). Reduced snacking (OR=2.08); female gender (OR=1.47); having a higher degree (OR=1.44); increased homemade meals (OR=1.31); the higher difference in the frequency of instant meals and snacks intake (OR=0.91); emotional eating (OR= 1.01); not increased alcohol dose intake (OR=0.57) and increased physical activity (OR=0.54) were independently associated with cognitive restraint. Perceived stress was independently associated with changes in the way of working or studying (OR=2.48); worse sleep quality (OR=2.22); younger age (OR=1.06) and emotional eating (OR=1.02). This study indicates that socioeconomic variables, lifestyle, and eating habits were independently associated with Brazilians eating behaviors and perceived stress during the quarantine.